Manajemen Industri Busana dan Kecantikan: Studi Lapangan SMK Tata Rias, Usaha Konveksi, dan LKP Tata Rias - Elvira Amin; Dina Ampera; Farihah (Media Manajemen Pendidikan, 2026)
This study aims to analyze the management of the fashion and beauty industries across three institutional settings: vocational education at a cosmetology-focused vocational high school, garment manufacturing enterprises, and non-formal skills training institutions in beauty services. The research was conducted from October to December 2025 at three locations in the Province of North Sumatra, Indonesia. A qualitative research design was employed, with data collected through in-depth interviews involving seven informants, comprising one vocational cosmetology teachers, three garment manufacturing business owners, and three managers of beauty training institutions. The study was supported by a review of academic literature published within the last five years. Data were analyzed using thematic analysis, including data reduction, theme development, and conclusion drawing. The findings reveal that management within the beauty sector emphasizes practice-based learning, hygiene and sanitation standards, salon management competencies, and industry partnerships. In contrast, garment manufacturing enterprises apply structured production management systems, industrial standard operating procedures, piece-rate wage systems, and manual quality control mechanisms. Beauty training institutions prioritize curriculum alignment with current industry demands, instructor certification, and structured industry internship programs. Supporting data indicate that labor demand in the beauty sector increased by 27%, while demand in the garment manufacturing sector rose by 18% over the past five years. This study provides a comprehensive overview of education and production management within Indonesia’s fashion and beauty industries, particularly in the context of Technical and Vocational Education and Training (TVET).